Area Differences in Regional Logistics Efficiency and the Law Governing Its Temporal and Spatial Evolution - Wenxue Ran; Ruli Liu; Shiwen Liu (Journal of Advanced Transportation)
Because logistics is an important service industry with regard to national economic development, the development level of this industry has emerged as one of the most significant indicators of a country or region’s comprehensive strength. An in-depth study of the regional differences in China’s logistics efficiency and its evolution law in time and space can help promote the high-quality development of the logistics industry. To this end, this study collects data pertaining to the development of the logistics industry in China’s eight economic regions during the period 2009–2018. Moreover, it uses DEA models to calculate the logistics efficiency of 31 provinces and cities in these eight economic regions. Results indicate the following: (1) affected by external environmental factors, the pure technical efficiency is underestimated and the scale efficiency and integrated technical efficiency are overestimated; (2) it reveals that residents’ consumption level and the total retail sales of social consumer goods are negatively correlated with regional logistics efficiency, whereas the regional per capita gross domestic product is positively correlated with regional logistics efficiency; (3) in terms of space, the logistics industry in the same region displays characteristics of high aggregation and cooperation, whereas serious segmentation and opposition are found among different regions. The logistics efficiency of China’s eight economic zones is unbalanced. It displays a pattern of high efficiency in the east and low efficiency in the west on the whole. Moreover, valuable suggestions were propounded to improve regional logistics efficiency in China.